An Improved, Scalable and Impurity‐Free Process for Lixivaptan. (29th September 2014) - Mu, Shuai; Niu, Duan; Liu, Ying; Zhang, Dashuai; Liu, Dengke; Liu, Changxiao
Abstract : An optimized synthetic method in high efficiency has been developed for the synthesis of lixivaptan from 2‐nitrobenzyl bromide and pyrrole‐2‐carboxaldehyde. The byproducts among this procedure and an unknown impurity in crude product were investigated. The byproducts were speculated by 1 H NMR or MS. The unknown impurity was characterized by 1 H NMR, 13 C NMR, and HRMS, confirming the structures as N ‐[3‐chloro‐4‐(5 H ‐pyrrolo[2, 1‐ c ][1, 4]benzodiazepine‐10(11 H )‐ylcarbonyl)phenyl]‐ N ‐(5‐fluoro‐2‐methylbenzoyl)‐5‐fluoro‐2‐methylbenzamide. Afterwards, the impurity was synthesized to make comparisons. The target product lixivaptan was obtained with 47.6% overall yield and 99.93% purity. This cost‐effective and environmentally friendly process is suitable for scale‐up production. Abstract :